Comparing pedestal structure in JET-ILW H-mode plasmas with a model for stiff ETG turbulent heat transport. (20th February 2023) - Field, A. R.; Chapman-Oplopoiou, B.; Connor, J. W.; Frassinetti, L.; Hatch, D. R.; Roach, C. M.; Saarelma, S.
Abstract : A predictive model for the electron temperature profile of the H-mode pedestal is described, and its results are compared with the pedestal structure of JET-ILW plasmas. The model is based on a scaling for the gyro-Bohm normalized, turbulent electron heat flux q e / q e, gB resulting from electron temperature gradient (ETG) turbulence, derived from results of nonlinear gyrokinetic (GK) calculations for the steep gradient region. By using the local temperature gradient scale length L T e in the normalization, the dependence of q e / q e, gB on the normalized gradients R / L T e and R / L n e can be represented by a unified scaling with the parameter η e = L n e / L T e, to which the linear stability of ETG turbulence is sensitive when the density gradient is sufficiently steep. For a prescribed density profile, the value of R / L T e determined from this scaling, required to maintain a constant electron heat flux q e across the pedestal, is used to calculate the temperature profile. Reasonable agreement with measurements is found for different cases, the model providing an explanation of the relative widths and shifts of the T e and n e profiles, as well as highlighting the importance of the separatrix boundary conditions. Other cases showing disagreement indicate conditions where other branches of turbulence might dominate. This article is part of a discussion meeting issue 'H-mode transition and pedestal studies in fusion plasmas'.